Plectorhinchus macrolepis (Actinopterygii: Haemulidae) in the western Atlantic Ocean - Adelir-Alves, J.; Spier, D.; Gerum, H. L. N.; Machado, L. F.; Spach, H. L.; Boza, B. R. [UNESP]; Oliveira, C. [UNESP] (Wiley-Blackwell, 2019)
Morphometric measurements, meristic counts and DNA barcoding identified the presence of a biglip grunt Plectorhinchus macrolepis in the western Atlantic Ocean. As the species is endemic to the tropical eastern Atlantic Ocean and has not previously been reported in the western Atlantic Ocean, we discuss the possible means by which it might have dispersed to the western Atlantic Ocean. Even though this species is not considered established in Paranagua Bay, we advocate monitoring of possible new individuals and other exotic fish species.
Keywords: biglip grunt; Brazil; DNA barcode; morphology; Paranagua Bay; Plectorhinchus macrolepis